An investigation into spatial and temporal aspects of transient stability in power systems with increasing renewable generation. (February 2020) - Hamilton, Robert I.; Papadopoulos, Panagiotis N.; Bell, Keith
Highlights: Renewables will have an increasing share of total generation in the future. Angular stability is significantly impacted by increased penetration of renewables. Locational aspects relating to renewables found to significantly impact stability. Synchronous generator cost is also found to impact angular stability boundary. System operators must consider operational and planning decisions carefully. Abstract: This paper investigates the impact of generator dispatch (dictated by cost) and locational aspects related to renewable generation connection and consequent disconnection of synchronous generation, on transient stability. As conventional synchronous generation (SG) is displaced by power electronic converter interfaced generation (PEC), the transient behaviour of the power system may change significantly due both to the changed power flows resulting from the different locations of renewables compared with thermal plant and the different dynamic characteristics of PEC. This paper uses an AC Optimal Power Flow (OPF) to determine credible, minimum cost dispatches of generation in a test network with increasing penetration of PEC in different locations. It is found that the critical locations of the system can vary significantly with respect to economic dispatch, location of disconnection of SG and location of PEC, highlighting the increasing temporal and spatial change in system dynamic behavior.